Why did self-employment increase so strongly in Germany? - Michael Fritsch; Alexander Kritikos; Alina Sorgner (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Germany experienced a unique rise in the level of self-employment in the first two decades following unification. Applying the non-linear Blinder-Oaxaca decomposition technique, we find that the main factors driving these changes in the overall level of self-employment are demographic developments, the shift towards service sector employment, and a larger share of population holding a tertiary degree. While these factors explain most of the development in self-employment with employees and the overall level of self-employment in West Germany, their explanatory power is much lower for the stronger increase of solo self-employment and of self-employment in former socialist East Germany.
Keywords: L26; D22; 330; self-employment; non-linear Blinder-Oaxaca decomposition technique; entrepreneurship; Germany